Study of PHBV/PP mixtures: Preparation and physicochemical characterization - HAMOUR, Noura (Biopolymer Applications Journal, 2023)
This research work consists in studying the structure-properties relationships of biopolymer mixtures based on poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and polypropylene (PP) elaborated by casting process according to the composition in terms of morphology, structure and thermal properties. The results showed a synergistic effect of glycerol addition on the thermal and morphological properties of the PHBV/PP blends.